(untitled) (Minang Chemistry Journal (MCJ), 2026)
A novel activated carbon modified with chitosan was fabricated and evaluated for the electrochemical adsorption of methylene blue dye from aqueous solutions. The modified carbon electrode showed enhanced capacitive properties and high affinity toward cationic dyes. Cyclic voltammetry and electrochemical impedance spectroscopy confirmed improved electrical conductivity. High removal efficiency (98%) was achieved within 30 minutes of electrolysis.